Rock and Popular Music / Politics, Policies, Intitutions - Bennett Tony; Crossberg Lawrence; Frith Simon; Shepherd John (Rouledge, 1993)
A unique collection suggesting significant new directions for the study of contemporary popular music. Preface, Acknowledgements, Introduction, Government and Rock, Popular Music and the Local State, Popular Music Policy: A Contested Area - The Dutch Experience, The English Canadian Recording Industry Since 1970, Making Music Local, Broadcasting: Music and Policies and Cultures and Communities, Radio Space and Industrial Time: The Case of Music Formats, Policing French-Language Music on Canadian Radio: The Twilight of the Popular Record Era?, Rock and Politics, Feminist Musical Practice: Problems and Contradictions, The Framing of Rock: Rock and the New Conservatism, Beat in the System, Aboriginal Rock Music: Space and Place, Name and Subject Index.